(untitled) (Journal of Medicine, 2008)
We report a 25-year-old man presenting with fever and weight loss for the six months along with anemia, hepatosplenomegaly and axillary lymphadenopathy. Laboratory investigations showed pancytopenia. Bone marrow and splenic aspiration was inconclusive, lymph node biopsy revealed LD bodies thus confirming visceral leishmaniasis. The case high lights the need of accepting lymph nodes as a site for diagnosing kala-azar and kala-azar lymphadenopathy is not as elusive as we think. Â Â DOI = 10.3329/jom.v9i2.1441 J MEDICINE 2008; 9 : 108-109